Municipal participation fund and development: an analysis of small municipalities in Brazil (Emancipação, 2020)
The objective of this study is to analyze the correlation between the Municipal Participation Fund (FPM) and socioeconomic development, as measured by Firjan Municipal Development Index (IFDM), by comparingthe data for 2013 and 2016 for small Brazilian municipalities. For that, FINBRA (Finance of Brazil) and Firjan Index data were used, measuring the dependence of the municipalities in relation to the transfers of the FPM and their correlation with the Firjan Index. As a corollary, the importance of the FPM was identified for the composition of the integrality of revenues of small municipalities, especially for the less developed municipalities. Moreover, unlike the other regions, in the North and Northeast there is a positivecorrelation between development and dependence on FPM.
Keywords: Development, Municipal Participation Fund, small municipalities.